Measuring Cultural Dimensions: External Validity and Internal Consistency of Hofstede's VSM 2013 Scales - Gerlach, Philipp; Eriksson, Kimmo (Frontiers in Psychology, 2021)
Cross-cultural comparisons often investigate values that are assumed to have long-lasting influence on human conduct and thought. To capture and compare cultural values across cultures, Geert Hofstede’s Cultural Dimensions Theory has offered an influential framework. Hofstede also provided a survey instrument, the Values Survey Module (VSM), for measuring cultural values as outlined in his Cultural Dimensions Theory. The VSM has since been subject to a series of revisions. Yet, data on countries have been derived from the original VSM — and not on one of the revised versions of VSM. We tested three scales (indulgence, power distance, and individualism) from the latest version, the VSM 2013, as part of a larger survey across 57 countries. Two main findings emerged. For one thing, country scores based on the VSM 2013 scales correlated only weakly with country scores of the same cultural dimensions obtained in a large previous study. Thus, the validity of the VSM 2013 is in doubt. For another thing, the internal consistency of the VSM 2013 scales was overall poor, indicating that the scales did not reliably measure well-defined constructs. We discuss implications for cross-cultural research.